PERAN GURU DAN BUDAYA SEKOLAH DALAM MEMBENTUK SISWA UNGGUL PADA SEKOLAH SMK HANG NADIM BATAM - Wasiman, Wasiman; Realize, Realize; Siagian, Mauli (PUAN INDONESIA, 2025)
Tri Dharma Perguruan Tinggi is the responsibility of every lecturer as a form of contribution to the community as a form of recognition of the knowledge they have so that the role of lecturers can be maximized in an effort to help educate the next generation of the nation. Community service is currently being carried out at SMK Hang Nadim Batam by taking the title The Role of Teachers and School Culture in Forming Excellent Students. The title was chosen because it was inspired by how important teachers are in forming an excellent generation and how school culture includes normative values and ethics that are currently starting to fade in schools and in society. School culture is a bond of norms that must be obeyed by every individual in the school such as the habit of greeting each other, getting used to discipline, getting used to living healthily by maintaining a clean environment, these are good habits that are now starting to fade in schools and society. The role of teachers as good examples is expected to restore the noble values of school culture that are currently starting to disappear, the question is why teachers, yes because teachers are the right figures who are role models in schools and society. School culture with the decreasing level of student discipline in various matters such as doing assignments at school and at home is also the responsibility of teachers assisted by parents of students so that they can work together in disciplining and cultivating students to be responsible for the tasks and work given to them.